A boundary problem for a single class of third-order equations (Eurasian Journal of Physics,Chemistry and Mathematics, 2022)
The boundary problem for a third-order equation of mixed type in a four-angle region is considered. Using the Galerkin method, under certain conditions, the existence of a weakly generalized solution in Sobolev's space was proved on the coefficients and the right side of the equation. Under the same conditions, the uniqueness of the generalized solution is proved